Bacterial expressed coat protein : development of a single antiserum for routine detection of Citrus tristeza virus - Nolasco, G.; Sequeira, Z. (Phytopathologia Mediterranea, 2002)
Citrus tristeza virus (CTV) causes one of the most important citrus diseases world-wide and has recentlybeen detected in Portugal. Early diagnosis based on immunoenzymatic techniques requires significant amounts ofreagents. This research describes the isolation of the coat protein gene of CTV, its expression in Escherichia coli as afusion protein containing an N-terminal (His)6 region and its use to raise rabbit polyclonal antibodies. These antibodiescould be used at dilutions higher than 1/80,000 at the detection stage in indirect ELISA tests and were alsoefficient for trapping the virus in ELISA and Immunocapture RT-PCR. These characteristics allowed the productionof diagnostic kits based solely on this source of antibodies. A detection spectrum and sensitivity similar to that of acommercial polyclonal antibody kit was achieved.